Biomechanical Comparison of a Notched Head Locking T-Plate and a Straight Locking Compression Plate in a Juxta-Articular Fracture Model - Bird, Guy; Glyde, Mark; Hosgood, Giselle; Hayes, Alex; Day, Robert (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective This investigation compared the biomechanical properties of a 2.0 mm locking compression notched head T-plate (NHTP) and 2.0 mm straight locking compression plate (LCP), in a simple transverse juxta-articular fracture model.Study Design Two different screw configurations were compared for the NHTP and LCP, modelling short (configuration 1) and long working length (configuration 2). Constructs were tested in compression, perpendicular and tension non-destructive four point bending and torsion. Plate surface strain was measured at 12 regions of interest (ROI) using three-dimensional digital image correlation. Stiffness and strain were compared between screw configurations within and between each plate.Results The LCP was stiffer than the NHTP in all three planes of bending and torsion (p < 0.05). The NHTP had greater strain than the LCP during compression bending and torsion at all ROI (p < 0.0005). The short working length was stiffer in all three planes of bending and in torsion (p < 0.05) than the longer working length for both plates. The long working length showed greater strain than the short working length at most ROI.Conclusion In this experimental model, a 2.0 mm LCP with two screws in the short fragment was significantly stiffer and had lower plate strain than a 2.0 mm NHTP with three screws in the short fragment. Extending the working length significantly reduced construct stiffness and increased plate strain. These findings may guide construct selection.
Keywords: T-plate; plate strain; locking compression; working length; juxta-articular; fracture model